On Energy Bound of Burgers Fisher Equation Under Dirichlet Boundary Condition - Dadang Amir Hamzah (Jurnal Rekayasa Teknologi dan Sains Terapan, 2021)
.In this paper the energy bound for the Burgers-Fisher equation under Dirichlet Boundary condition is determined. The boundedness of the reaction term plays a significant role in determining the energy bound. A number of inequalities are employed in deriving of the bound.